The perceptual and neuronal stability of the rubber hand illusion across contexts and over time - Bekrater-Bodmann, Robin; Foell, Jens; Diers, Martin; Flor, Herta (Brain research, 2012)
The rubber hand illusion (RHI) offers the opportunity to systematically manipulate the experience of embodiment, which is here used to describe the subjective integration of an external object into one's body representation. Among the cortical regions involved in the processing of body perception, the ventral premotor cortex seems to be crucial in the integration of visuotactile stimuli. However, it is not known if the perceived vividness of the RHI is a trait or a state variable. In the present study, we varied the setup of the RHI to test the stability of perception. The illusion was induced in two different contexts, with either a horizontal or vertical displacement of the rubber hand in respect to the real hand. Further, the RHI was induced twice with an interval of at least six months and long-term changes on the perceptual and behavioral level were evaluated. Finally, we measured the long-term stability of cortical activity during the induction of a vertical RHI using functional magnetic resonance imaging. We found that a vertical setup induced higher ratings of illusory embodiment of the rubber hand than a horizontal setup, but the responses to both setups were significantly correlated. There was high intra-individual long-term stability of the subjective perception of illusory embodiment but a lower stability on the behavioral level. The functional magnetic resonance imaging data suggest temporally stable ventral premotor cortex processing. These results indicate that dynamic changes in perceived limb ownership by the induction of the RHI are trait-like.